2012
DOI: 10.1007/s00247-012-2406-2
|View full text |Cite
|
Sign up to set email alerts
|

Doxycycline sclerotherapy in children with lymphatic malformations: outcomes, complications and clinical efficacy

Abstract: Doxycycline is a safe and effective sclerosant agent for treating LMs in children, with a low complication rate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
43
0
14

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(61 citation statements)
references
References 28 publications
4
43
0
14
Order By: Relevance
“…6 Sclerotherapy has emerged as a promising alternative to surgery for the treatment of LMs in children during the past 30 years. Agents used include bleomycin, 7,8 alcoholic solution of zein (Ethibloc), 9,10 interferon α2a, 11 hypertonic saline solution, 12 fibrin sealant, 13 1% polidocanol, 14 acetic acid, 15 ethanol, 16 doxycycline, [17][18][19][20][21] and OK432. 2,3,[22][23][24][25][26][27][28] Although bleo mycin may be useful for treating microcystic lesions, 29 it has fallen out of favor for treating macrocystic LMs because of its risk of pulmonary fibrosis, since alternative agents are available.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…6 Sclerotherapy has emerged as a promising alternative to surgery for the treatment of LMs in children during the past 30 years. Agents used include bleomycin, 7,8 alcoholic solution of zein (Ethibloc), 9,10 interferon α2a, 11 hypertonic saline solution, 12 fibrin sealant, 13 1% polidocanol, 14 acetic acid, 15 ethanol, 16 doxycycline, [17][18][19][20][21] and OK432. 2,3,[22][23][24][25][26][27][28] Although bleo mycin may be useful for treating microcystic lesions, 29 it has fallen out of favor for treating macrocystic LMs because of its risk of pulmonary fibrosis, since alternative agents are available.…”
Section: Introductionmentioning
confidence: 99%
“…This difference is likely attributable to inherent differences in the agents themselves, and not to our practice of leaving OK432 in the cyst, as most institutions that do not aspirate doxycycline still do not report marked postoperative swelling. 18,20,21,36 Despite parental counseling about this early and short-lived side effect, 2 patients in the OK432 group required readmission for analgesia and hydration. Serious adverse events that required hospitalization have been reported for both OK432 22,25,26,28 and doxycycline sclerotherapy, 20,21 but in our series only patients in the OK432 group required readmission.…”
mentioning
confidence: 99%
“…They occur most commonly within the head and neck but are rare in the orbit 4. Histologically, LMs consist of cystic dilatation of lymphatic channels lined by vascular endothelium; they contain proteinaceous fluid 6. They are thought to be a result of erroneous embryogenesis 5.…”
Section: Discussionmentioning
confidence: 99%
“…Percutaneous injection of lyophilized group A Streptococcus pyogenes OK432 and doxycycline has been successful in the treatment of large, nonresectable lymphangiomas in children. 1,11 MLMs have been reported to regress prenatally. 12 The same study also suggested that neonatal patients with symptoms require surgery, whereas those without symptoms can be observed.…”
Section: Discussionmentioning
confidence: 99%